Interactions of the Chemokine CCL5/RANTES with Medium Sized Chondroitin Sulfate Ligands - Deshauer, Courtney (Structure, 2015)
Interactions of the chemokine CCL5 (RANTES) with glycosaminoglycans (GAGs) are crucial to the CCL5-mediated inflammation process. However, structural information on interactions between CCL5 and longer GAG fragments is lacking. In this study, the interactions between oligosaccharides derived from chondroitin sulfate and a dimeric variant of CCL5 were investigated using solution NMR. The data indicate that, in addition to the BBXB motif in the 40s loop, GAGs also contact residues in the N-loop in a manner similar to interactions between chemokine and the receptor N-terminus, and leading to possible stabilization of the dimer. Using TEMPO-tagged hexasaccharides, the binding orientation of the hexasaccharides was shown to be highly dependent on the sulfation pattern of the GalNAc groups. Finally, a model of the CCL5 dimer complexed to CS hexasaccharides was constructed using paramagnetic relaxation enhancement and intra- and inter-molecular NOEs constraints.